Determination of Pollination Ecology and Fruiting Behaviour in Strychnos nux-vomica L. (Loganiaceae) - Madhab Chandra Behera (Current Topics in Agricultural Sciences Vol. 2, 2021)
Flowers of Strychnos nux-vomica are small, greenish-white, bisexual, nectariferous and emit mild sweet odour. They open during evening hours and offer pollen and nectar to the visitors. Bees, flies, wasps, butterflies, beetles and birds are the pollinators. Apis dorsata and Euploea core are the principal one and makes diurnal visit between 7.00-17.00 hours. The anther dehiscence starts at 16.00-16.15 hours. The capitate stigma receptive to pollen germination at 17.30-18.00 hours and remain in receptive state one day after complete anther dehiscence. Breeding system is mixed type. Flowers favour cross-pollination (29.78-60.26%) however selfing is also possible (17.94-39.74%). Results pertaining to floral biology, reproductive phenology, mating system and pollinators will be much helpful in developing breeding strategies for genetic improvement as well as conservation in the wild.